STATUS OF THE RURAL COMMUNITY ON THE LADDER OF PUBLIC PARTICIPATION. THE CASE OF WASTE MANAGEMENT PROGRAM IN MOJOSARI VILLAGE, BOJONEGORO - Hidayah, Nurul; Meidiana, Christia; Firdausiyah, Nailah; Ghosh, Ratan Kumar; Amalia, Rizky (Directorate of Research and Community Service (DRPM), 2024)
The success of waste management cannot be separated from the community's participation. The community's involvement in waste management is still not significantly apparent. Community participation in rural waste management program was investigated in this study since the waste reduction activities still involve waste open burning and burying in the yard which is harmful for the environment. A research model was designed, and a questionnaire was distributed among 112 households (HHs) to analyze their participation in rural waste management programs. A semi-structured questionnaire survey, focus group discussions, and key informant interviews were adopted to acquire qualitative information. The analytical framework includes mass balance analysis (MBA) and Arnstein’s participation (APL) ladder. MBA was applied to measure the current waste reduction rate of each HH, while APL was used to evaluate community participation level in this program. The findings reveal that the average waste reduction is 0.48 kg/HH/day, contributing to a total waste reduction of 17.94 kg/day in the village (24.39% of total waste generation). Measurement using APL unfolds that the extant community participation in Mojosari Village, Bojonegoro Regency, corresponds to a non-participation continuum where villagers are misled by pseudo and tokenistic participation leading to unequal benefit-sharing. Based on these findings, the researchers challenge that communities’ engagement in rural waste management mainly relies on community cadres concerning environmental subjects as well as communities’ economic background. It is concluded where economically weak communities and manipulative figures exist, ensuring a higher community participation level is more challenging